2016
DOI: 10.1136/bjsports-2016-096456
|View full text |Cite
|
Sign up to set email alerts
|

Structural pathology is not related to patient-reported pain and function in patients undergoing meniscal surgery

Abstract: BackgroundThe relationship between meniscal tears and other joint pathologies with patient-reported symptoms is not clear. We investigated associations between structural knee pathologies identified at surgery with preoperative knee pain and function in patients undergoing arthroscopic meniscal surgery.MethodsThis study included 443 patients from the Knee Arthroscopy Cohort Southern Denmark (KACS), a prospective cohort following patients 18 years or older undergoing arthroscopic meniscal surgery at 4 hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…The facts that only one-fourth of the patients showed a positive McMurray test, and conversely 49% of the patients reported mechanical symptoms, suggest that there is a need for further definition of the mechanical symptoms and description of the size, type and location of the meniscus tear. 29 In the same way, the timing to consider arthroscopic surgery can be a source of controversy. Three months from the onset of symptoms was agreed on as a general rule as it is the time generally adopted in the RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…The facts that only one-fourth of the patients showed a positive McMurray test, and conversely 49% of the patients reported mechanical symptoms, suggest that there is a need for further definition of the mechanical symptoms and description of the size, type and location of the meniscus tear. 29 In the same way, the timing to consider arthroscopic surgery can be a source of controversy. Three months from the onset of symptoms was agreed on as a general rule as it is the time generally adopted in the RCTs.…”
Section: Discussionmentioning
confidence: 99%
“… 2016 , Tornbjerg et al. 2017 ). Of 8 major randomized controlled trials (RCTs) assessing surgical treatment of degenerative meniscal disease in patients with or without osteoarthritis (Moseley et al.…”
mentioning
confidence: 99%
“…In a randomised, placebo-controlled study of patients with knee pain that was degenerative in origin, the prevalence of mechanical symptoms was 49 % after arthroscopic meniscus resection and 43 % in the placebo group (32). In another study, it turned out that pre-operatively self-reported pain and functional impairment were not associated with structural knee pathology, including degenerative meniscus injury, detected by subsequent arthroscopy (33).…”
Section: Symptoms and Findings For Meniscus Injuriesmentioning
confidence: 97%